1985
DOI: 10.1017/s0007485300014358
|View full text |Cite
|
Sign up to set email alerts
|

Olesicampe monticola (Hedwig) (Hymenoptera: Ichneumonidae) redescribed together with notes on its biology as a parasite of Cephalcia lariciphila (Wachtl) (Hymenoptera: Pamphiliidae)

Abstract: The sawfly Cephalcia lariciphila (Wachtl) is a pest of larch (Larix spp.) that has recently become widespread in Britain. Before taking measures to control the sawfly the status of parasites in the infestations was investigated. The only insect parasite species found was the ichneumonid Olesicampe monticola (Hedwig), which is new to Britain. As this insect is taxonomically so poorly known it is redescribed from specimens collected in South Wales. The preliminary biological observations show O. monticola to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A number of groups have radiated to exploit the larvae of other holometabolous insects occurring in similar situations. For example, species of the genus Olesicampe develop in the larvae of tenthredinoid symphytans (Pschorn-Walcher & Zinnert, 1971;Billany et al, 1985) and species of Lemophagus attack chrysomelids (Carlson, 1979). Oviposition is into the larva of the host (Fisher, 1959;Frilli, 1965).…”
Section: T H E General Biology Of Campoplegine Ichneumonidsmentioning
confidence: 99%
“…A number of groups have radiated to exploit the larvae of other holometabolous insects occurring in similar situations. For example, species of the genus Olesicampe develop in the larvae of tenthredinoid symphytans (Pschorn-Walcher & Zinnert, 1971;Billany et al, 1985) and species of Lemophagus attack chrysomelids (Carlson, 1979). Oviposition is into the larva of the host (Fisher, 1959;Frilli, 1965).…”
Section: T H E General Biology Of Campoplegine Ichneumonidsmentioning
confidence: 99%
“…Barbosa and Schaefer (1997) assessed this hypothesis in an analysis of invasions by four species of lymantriid moth in North America and concluded that there was little evidence to support the view that impacts were greater in the absence of the full spectrum of natural enemies. Populations were subsequently regulated to very low densities by an accidentally intro-duced parasitoid Olesicampe monticola (Hymenoptera: Ichneumonidae) (Billany & Brown 1980;Billany et al 1985), thereby restoring a specific host-parasitoid relationship that is a normal factor in the natural range of the sawfly in Europe. Extensive tree damage was observed in both situations and, in both cases, a baculovirus (nucleopolyhedrovirus) was introduced, either deliberately (Canada: Bird & Elgee 1957), or by natural appearance and spread (Wales: Entwistle et al 1983).…”
Section: Great Britain As An Example Of a Region Where Pest Infestatimentioning
confidence: 99%